The Impact of precolonial ethnic institutions and colonial rules in Africa - LEE, Sang eun (KDI School, 2022)
With the ongoing importance on the role of traditional chiefs, the paper investigates the impact of precolonial centralization of ethnic groups on the public goods provision and trust level toward chiefs today. With the question whether the succession of the traditional institutions is affected by the type colonial rule either by Britain or France, I match Afrobarometer data with Murdock’s Ethnographic Atlas and other data sets. The paper documents three main findings. First, I find a strong positive association between precolonial ethnic political centralization and trust toward local chiefs today among Anglophone countries, but a negative association among Francophone countries. Second, there is a strong positive association for both countries colonized by Britain or France in terms of infrastructure. Third, I find a strong positive association between precolonial centralization and wellbeing among Anglophone countries, but no impact in Francophone countries. The similar pattern of positive and robust association on the infrastructure implies that precolonial centralization was conducive to African public goods provision with different colonial rule having a limited impact. On the other hand, the opposite pattern of association on the trust toward local chiefs implies that different colonial rule has affected social capital of contemporary traditional institutions differently. Under the assumption that local accountability mechanism holds, positive association among Anglophone countries implies that the precolonial institutions have been more likely to survive under British indirect rule compared to French direct rule. The findings suggest that contemporary African development, particularly access to public goods provision or local chieftaincy system are linked to the preexisting ethnic institutions as well as the legacies of colonialism.
Thesis(Master) -- KDI School: Master of Development Policy, 2022
Keywords: Ethnic relations--Africa; Economic development--Africa